Bioconservation of iron and enhancement of antioxidant and antibacterial properties of chicken gizzard protein hydrolysate fermented by Pediococcus acidilactici ATTC 8042. (12th November 2020) - Ali, Ali Muhammed Moula; Gullo, Maria; Rai, Amit Kumar; Bavisetty, Sri Charan Bindu
Abstract: BACKGROUND: The poultry industry is one of the fastest growing sectors, and it generates considerable quantities of chicken gizzards (CG) every day. However, due to their hard texture and high microbial load, and due to cultural beliefs, they are not preferred by consumers. Chicken gizzards are a substantial source of proteins, iron, and other nutrients, which can be used effectively to produce nutraceuticals, rich in peptides (antioxidants and antibacterial), bio‐iron, essential free amino acids, and fatty acids vital for human health. RESULTS: Lactic acid fermentation of CG by Pediococcus acidilactici ATTC 8042 increased the antioxidant activity of 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH), azino‐bis (3‐ethylbenzothiaziline‐6‐sulphonic acid) (ABTS), and ferric reducing antioxidant power (FRAP) by up to 26 times compared with unfermented CG ( P < 0.05). The amount of hydrolysis and solvents (ethanol and water) used for extracting protein hydrolysates significantly affected the antioxidant properties. Moreover, fermented CG showed a negligible reduction in bio‐iron (2–3%) compared with heat‐processed CG (85 °C for 15 min), in which bio‐iron was reduced by up to 20.3% ( P < 0.05). The presence of unsaturated fatty acids such as C20:4 and C22:4 n‐6 indicated a low level of lipid oxidation. CONCLUSION: Fermented CG, with its reasonably high antioxidant and antibacterial activity, together with a substantial amount of bio‐iron and other nutritional components can serve as a functional food or feed additive to reduce oxidative stress and to treat iron deficiency. © 2020 Society of Chemical Industry